Identification of Adverse Drug Reactions of Antidiabetic Drugs Among Hospitalized Elderly Patient with Diabetes - Udhiyati, Aida; Rahmawati, Fita (Majalah Farmaseutik, 2024)
The pharmacologic management of many acute and chronic conditions and the aging population have contributed to increasing medication use among elderly patients, this situation may lead to drug-related problems (DRPs) especially adverse drug reactions (ADR). This study aims to identify ADR of antidiabetic drugs among hospitalized elderly patient with diabetes. This descriptive observational study with a cross sectional design involved 98 geriatric patients at UGM Academic Hospital that admission between January to December 2021. The inclusion criteria were patients aged above 60 years, has complete medical record and patient was diagnosed with diabetes. WHO-UMC causality assessment criteria and Hartwig and Siegel’s scale was used for the assessment of causality and severity of ADRs, respectively. Number of patient who had experienced ADR were 15 (15.31%) patients with total ADR event were 15 (15.31%) ADRs. The result recorded 11 (11.22%) patients experienced ADR with causality category possible and severity category moderate, and 4 (4.09%) patients experienced ADR with causality category possible and severity category mild. Clinical manifestation of those ADR were nausea, heartburn, hypokalemia and hypoglycemia. The suspected antidiabetic drugs that caused ADR were metformin and insulin. Given pharmaceutical care among elderly with diabetes is pivotal to prevent ADR of antidiabetic drugs.